Household risk strategies during a pandemic – experiences from the 1918 influenza pandemic. Issue 1 (2nd January 2023) - Andersson, Lars-Fredrik; Eriksson, Liselotte
ABSTRACT: In 2020, The COVID-19 crisis has put great pressure on the economy worldwide. Only time can tell whether the COVID-19 crisis will have permanent effects on corporate and household behaviour and how it will affect society at large. This article examines historical experiences of how households managed the financial consequences of rising mortality during the 1918 influenza pandemic. We find that the previous pandemic led to an immediate and major increase in primarily small-sum industrial life insurance policies designed for blue-collar workers. The increase in new policies did not, however, have a lasting effect. By the time the pandemic had faded, the number of policies had dropped to below pre-pandemic conditions. This historical experience underlines the fact that there are limits to the extent to which even a major shock, such as a pandemic, can lead to behavioural change among households as currently being predicted in relation to COVID-19.